As fundações de apoio às universidades públicas: efeitos da reforma do Estado na educação superior brasileira - Protetti, Fernando Henrique; Vaidergorn, José [UNESP] (My University, 2011)
The article discusses support foundations for public universities starting from the effects of State reform on Brazilian higher education in the 1990s. Based on Max Weber’s Comprehensive Sociology and on bibliographical and documentary research, it socio-historically circumscribes the management model of State administration and the concept of foundation. As one identifies the intersections between the guidelines of support foundations and the purposes of managerial administration, one understands the significance of such institutions for university management and the tendency towards commodification of Brazilian higher education.

O artigo tem a finalidade de introduzir a discussão sobre as fundações de apoio às universidades públicas a partir dos efeitos produzidos pela reforma do Estado na Educação Superior brasileira na década 1990. Fundamentado na Sociologia Compreensiva de Max Weber e em pesquisa documental e bibliográfica, delimita sócio-historicamente o modelo gerencial de administração do Estado e o conceito de fundação. Ao identificar intersecções entre as orientações das fundações de apoio e os pressupostos da administração gerencial, apreende o significado dessas instituições na gestão universitária e a tendência à mercantilização da Educação Superior brasileira.
Keywords: Fundações de Apoio; Universidades Públicas; Administração Gerencial; Educação superior- mercadoria